Malaysia-Myanmar relations 1997-2002 : a 'prosper thy neighbour' strategy / Qasim Ahmad - Ahmad, Qasim (Universiti Teknologi MARA, Shah Alam, 2004)
There might well be elements in the modern history of both Malaysia and Myanmar that could have played a significant role in paving the way for the two countries to get along rather amicably in the closing decades of the last century. That period, starting from the late 1980s, was a time when Myanmar found itself at the receiving end of serious and persistent international criticisms. Myanmar was censored for the heavy-handed way in which she handled internal opposition and dissension within the country. The military administration in Myanmar had taken actions against the participants of the pro democracy movement which started in August 1988. The Myanmar government was again taken to task after it failed to recognize the 1990 election results in which the Aung San Suu Kyi led National League for Democracy won a convincing victory, capturing 392 out of the 485 seats contested